2022
DOI: 10.3390/foods11203159
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic and Metabolomic Analyses Reveal the Regulatory Effect and Mechanism of Tea Extracts on the Biosynthesis of Monascus Pigments

Abstract: Monascus pigments (MPs) are natural edible pigments with high safety and strong function, which have been widely used in food and health products. In this study, different types of tea extracts (rich in polyphenols) were used to regulate the biosynthesis of MPs. The results showed that 15% ethanol extract of pu-erh tea (T11) could significantly increase MPs production in liquid fermentation of Monaco’s purpureus M3. Comparative transcriptomic and metabolomic analyses combined with reverse transcription-quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…As a characteristic fungus in Hongqu (red yeast rice), M. purpureus always has a certain abundance in the whole fermentation process of Hongqu aged vinegar. It was previously reported that Monascus would produce a variety of functional secondary metabolites, including pigments, γ-aminobutyric acid (GABA) and monacolin K, most of which are believed to have antibacterial, antihypertensive and other health effects [32]. S. aogashimaense was firstly found in the fermentation of Hongqu aged vinegar, which was previously identified as the prolific producers of a wide range of secondary metabolites, including class compounds of peptide, glycolipid, polyketide and organic acid [33].…”
Section: Discussionmentioning
confidence: 99%
“…As a characteristic fungus in Hongqu (red yeast rice), M. purpureus always has a certain abundance in the whole fermentation process of Hongqu aged vinegar. It was previously reported that Monascus would produce a variety of functional secondary metabolites, including pigments, γ-aminobutyric acid (GABA) and monacolin K, most of which are believed to have antibacterial, antihypertensive and other health effects [32]. S. aogashimaense was firstly found in the fermentation of Hongqu aged vinegar, which was previously identified as the prolific producers of a wide range of secondary metabolites, including class compounds of peptide, glycolipid, polyketide and organic acid [33].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, comparative transcriptomic analyses have been applied to investigate gene transcription in this fungus under different fermentation conditions (such as different carbon/nitrogen sources, special additives, light treatment, etc.) [ 12 , 13 , 14 , 15 ]. These studies often concentrated on the biosynthesis of MPs, although several reports also investigated the expression of the CIT pathway in different M. purpureus strains and fermentation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, MRPs have beneficial effects in controlling blood cholesterol and preventing diabetes, obesity, and cancer [6,7]. MRPs can be added to most products, as a safe food coloring according to production needs [8]. MRPs are widely used in products such as meat, wine, and pasta.…”
Section: Introductionmentioning
confidence: 99%